Making PBL teams more effective with Scrum - Carvalho, José Dinis (2019)
Scrum is a project management methodology very popular in the software industry with good results in terms of team work effectiveness. Scrum is based on important team work values such as commitment, courage, focus, openness and respect and can be described in three different dimensions: Scrum team; Scrum Events; and Scrum artefacts. This paper aims to analyse the implementation of scrum approach in a project based learning context in higher education. The scrum approach was applied in the fourth year of the Industrial Engineering and Management (IEM) degree program, where teams of students developed a PBL project in an industrial context during the first semester. The research methodology focused on a qualitative approach. Semi-structured interviews were carried out to the Scrum Team (scrum master, product owner and the student team). Scrum Events were analysed through direct observation and Scrum Artefacts (Product Backlog, Sprint Backlog and Increment) were analysed based on a document analysis. The results of this study contribute to understand the effectiveness of the application of Scrum to complex PBL learning environments. The results presented in the study provided important inputs to improve the way PBL student teams manage themselves as well as their projects.